Retroviral foamy virus gag induces parkin-dependent mitophagy - Shanshan Wang; Tongtong Du; Jun Yan; Yingcheng Zheng; Yinglian Tang; Juejie Wu; Qian Xu; Shanshan Xu; Luo Liu; Xiong Chen; Song Han; Jun Yin; et al. (Retrovirology)
Abstract Background Prototype foamy virus (PFV) is a complex retrovirus that can maintain latent infection for life after viral infection of the host. However, the mechanism of latent infection with PFV remains unclear. Our previous studies have shown that PFV promotes autophagy flux, but whether PFV causes mitophagy remains unclear. Results In this study, we demonstrated that PFV infection damages mitochondria, increases mitochondria reactive oxygen species (mtROS) production, and induces mitophagy in a time-dependent manner. Further investigation revealed that PFV Gag is a crucial protein responsible for triggering mitophagy. The overexpression of Gag leads to mitochondrial damage and stimulates mitophagy in a dose-dependent manner. Additionally, overexpression of Gag activates the PINK1-Parkin signaling pathway, while the knockdown of Parkin inhibits Gag-induced mitophagy. Furthermore, Rab5a was significantly upregulated in cells overexpressed Gag, and the inhibition of Rab5a reversed the effects of Gag-induced mitophagy. Conclusions Our data suggested that PFV can induce mitophagy and Gag induces Parkin-dependent mitophagy by upregulating Rab5a. These findings not only enhance a better understanding of the foamy virus infection mechanisms but also provide critical insights into novel virus-host cell interactions.